2019
DOI: 10.21873/anticanres.13394
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Role of DCLK1 in Pathogenesis, Diagnostic Procedures and Prognostic Stratification of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the second most prevalent type of cancer among males and the third among females. CRC recurrence and poor prognosis may be related to the prevalence of chemotherapy-resistant cancer stem cells (CSCs). Recent studies have indicated the role of doublecortin-like kinase 1 (DCLK1) protein as a marker of CSC in CRC. This review focuses on the role of DCLK1 in CRC. Long-lived DCLK1-positive tuft cells can function as cancer-initiating cells. Numerous studies have shown DCLK1 overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
(85 reference statements)
1
19
0
Order By: Relevance
“…However, some studies have shown that CD44 overexpression has been correlated with worse OS of patients with CRC (Wang et al 2019 , 2017 ). Similarly, several studies show a positive correlation between high DCLK1 expression and CRC clinicopathological characteristics and poor OS (GZIL et al 2019a , b ). However, Dai T. et al’s study reveals that a high DCLK1 expression in CRC tissue could play a protective role against tumor progression and correlates with longer survival time (Dai et al 2018 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, some studies have shown that CD44 overexpression has been correlated with worse OS of patients with CRC (Wang et al 2019 , 2017 ). Similarly, several studies show a positive correlation between high DCLK1 expression and CRC clinicopathological characteristics and poor OS (GZIL et al 2019a , b ). However, Dai T. et al’s study reveals that a high DCLK1 expression in CRC tissue could play a protective role against tumor progression and correlates with longer survival time (Dai et al 2018 ).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, it is well known that CSCs are insensitive to the current drug regimens. CSCs in CRC are identified via a group of surface markers, such as CD44, CD133, ANXA2, CD24, DCLK1, Lgr5, ALDH1, Nanog, Oct-4, SOX-2, and EpCAM (Leng et al 2018 ) (Gzil et al 2019a , b ). Some of these markers could have a potential clinical role in predicting pathological stage, therapy resistance, and cancer recurrence in patients with colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Very recent studies demonstrated that DCLK1 plays an important role in epithelialmesenchymal transition and is associated with drug resistance as well as poor prognostication of colorectal cancer. 24,32,49,52,68,84 In this investigation, DCLK1 was diffusely expressed in canine intestinal adenomas and infrequently detectable in intestinal adenocarcinomas. In general, papillary CRCs showed a higher expression of DCLK1 in the luminal aspects of the tumor than in the invasive areas.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, it has been reported that ZEB1 is also a target gene of miR-124-3p and the upregulation of ZEB1 could promote EMT and stemness by acting as the most important EMT-activating transcription factor [39] . DCLK1, a member of the protein kinase superfamily and the double cortin family, is highly expressed in several types of cancers and has been recently identi ed as a tumor stem cell marker in CRC [40,41] .…”
Section: Discussionmentioning
confidence: 99%